Inflation as a Trigger for Changes in Financial Behaviour People Shift from Saving to Investing - Leroy Samy Uguy; Esther Kembauw; Maulida Nurfajrianti; Ridwan Masihuwey (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Investment is a financial strategy chosen by individuals to preserve and grow wealth. In recent years, investment activity in Indonesia has increased amid a downward trend in inflation. This reflects a shift in financial behaviour, where inflation is no longer seen solely as a threat but also as a driver for moving from saving to investing. As people become aware of inflation’s impact on purchasing power, they increasingly allocate funds to more profitable investment instruments. This study uses a behavioural finance approach and macroeconomic data from 2019 to 2024 to illustrate the pattern. The analysis shows that declining inflation, along with rising financial literacy, has significantly contributed to investment growth.